A process for preparing an environmentally-friendly magnesium oxide composite board based on retired wind power blade solid waste
Patent Information
- Application Number
- CN202611214002.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0010]本发明的目的在于提供一种基于退役风电叶片固废制备环保氧化镁复合板材的工艺,以改善退役风机叶片固废在氧化镁复合板材中应用时存在的界面相容性差、分散不均以及火灾工况下树脂瞬态热解导致板材破坏的问题
本发明提供的基于退役风电叶片固废制备环保氧化镁复合板材的工艺,能够改善背景技术中提及的叶片粉碎料常温固有缺陷、传统增强填料性能-成本难以兼顾以及火灾高温下树脂瞬态热解引发板材破坏的问题,具体如下:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization and building materials technology, specifically a process for preparing environmentally friendly magnesium oxide composite panels based on solid waste from decommissioned wind turbine blades. Background Technology
[0002] In building fire compartmentation systems, fire-resistant partitions, smoke exhaust duct liners, fire-resistant ceilings, and fire-resistant door core panels are key fire-resistant components. Fire-resistant partitions are used to divide independent fire compartments and suppress the horizontal and vertical spread of fire; smoke exhaust duct liners are installed on the inner walls of smoke exhaust ducts to ensure the structural integrity of the smoke exhaust channel during a fire; fire-resistant ceilings shield the upper space of floors, preventing fire from spreading along the ceiling cavities; and fire-resistant door core panels fill the interior of fire doors, maintaining the integrity and thermal insulation performance of the door leaf within a limited fire resistance time.
[0003] These components require stringent fire resistance conditions: during a fire resistance duration of 1–3 hours, the fire-facing surface must withstand temperatures exceeding 800°C, while the temperature rise on the unfired surface needs strict control. Simultaneously, the component must not collapse or allow flame penetration. Therefore, the core layer material used to manufacture these components must meet Class A non-combustible requirements and maintain good mechanical properties and structural integrity under high-temperature conditions.
[0004] Magnesium oxide-based composite boards use inorganic magnesium cement as a binder and are naturally non-combustible and lightweight, making them a common material for preparing the core boards of the aforementioned fireproof components. However, magnesium oxide-based boards are relatively brittle and have low flexural strength, making them prone to cracking under thermal stress or external impact. When used alone, they cannot meet the long-term mechanical integrity requirements of components. Therefore, reinforcing fibers are usually added during the production process to improve the toughness and flexural strength of the boards.
[0005] Currently, the mainstream reinforcement solutions in the industry fall into two categories: one involves adding organic plant fibers such as wood fiber. While wood fiber can improve the toughness of the board, it is itself flammable and easily carbonizes under high temperatures, forming internal defects that impair the fire resistance integrity of the board. The other category uses virgin glass fiber. Virgin glass fiber is non-flammable and has excellent reinforcement effects, but its preparation energy consumption and production costs are high, which is not conducive to the large-scale, low-cost application of the board. Therefore, developing new reinforcing fillers that combine non-flammability, good reinforcement effects, and cost advantages is key to improving the overall performance of magnesium oxide composite boards.
[0006] Decommissioned wind turbine blades are primarily composed of glass fiber reinforced thermosetting resin composites, containing a large amount of glass fiber. Using the glass fiber from decommissioned blade waste as a reinforcing filler in magnesium oxide (MgO) sheets would, on the one hand, achieve the resource-based disposal of policy-driven industrial solid waste, and on the other hand, provide low-cost recycled reinforcing raw materials for MgO sheets, enabling high-value disposal of decommissioned wind turbine blade waste and improving the performance of MgO sheets. However, directly applying decommissioned wind turbine blade waste to the preparation of MgO composite panels for fire-resistant components still presents several key technical challenges: First, after the retired wind turbine blades are mechanically crushed, a mixture of particles and fiber bundles is obtained: the surface of the particles and fiber bundles is coated with cured epoxy resin or unsaturated polyester resin. This inert organic layer has poor interfacial compatibility with the inorganic magnesium cement matrix, resulting in low interfacial bonding strength. At the same time, the glass fiber bundles in the crushed material have a disordered morphology and uneven aspect ratio distribution. They are prone to entanglement and clumping during the slurry mixing stage, making it difficult to disperse evenly in the matrix. This forms stress concentration areas inside the product, causing deterioration of mechanical properties.
[0007] Secondly, traditional reinforcing fillers generally present a contradiction between performance and cost. Magnesium oxide fireproof boards require reinforcing fillers to be both non-combustible and economical: organic plant fibers have a decent toughening effect, but their fire resistance is lacking; virgin glass fiber has excellent fire resistance and reinforcing properties, but its high cost restricts its large-scale promotion.
[0008] Third, under rapid temperature rise conditions in a fire, the resin layer coating the glass fiber surface of the blade shredded material undergoes rapid pyrolysis, inducing coupled damage in the dense magnesium oxide hardened matrix: on the one hand, the large amount of volatile gases generated by resin pyrolysis cannot escape in time, forming high gas pressure inside the board, inducing local micro-explosions and delamination, causing failure of fireproof partition integrity; on the other hand, after the resin layer is ablated and carbonized at high temperature, micron-level gaps are formed between the glass fiber and the matrix, the fiber reinforcement effect is lost, forming heat and flame transfer channels, reducing the load-bearing capacity of the board under fire conditions, and increasing the risk of component collapse.
[0009] Based on the above situation, there is an urgent need to provide a process for preparing environmentally friendly magnesium oxide composite panels using solid waste from decommissioned wind turbine blades, in order to improve the above technical problems and have important engineering application value. Summary of the Invention
[0010] The purpose of this invention is to provide a process for preparing environmentally friendly magnesium oxide composite boards based on solid waste from decommissioned wind turbine blades, so as to improve the problems of poor interfacial compatibility, uneven dispersion, and damage to the boards caused by transient pyrolysis of resin under fire conditions when solid waste from decommissioned wind turbine blades is used in magnesium oxide composite boards.
[0011] The objective of this invention is achieved through the following technical solution: A process for preparing environmentally friendly magnesium oxide composite panels based on solid waste from decommissioned wind turbine blades includes the following steps: S1: Mechanically crush the retired wind turbine blades and place them in a low-temperature plasma treatment chamber for treatment in a mixed atmosphere of oxygen and nitrogen. During the treatment process, the crushed material is continuously turned over to obtain activated crushed material. S2: The activated fragments obtained in step S1 are immersed in an active magnesium oxide-magnesium chloride precursor solution, stirred and reacted, and then taken out for pre-curing to obtain seeded fragments; the precursor solution contains nano-magnesium hydroxide nucleation promoter; S3: Immerse the seeded fragments obtained in step S2 in the functional hybrid slurry, stir, and then take them out and dry them to obtain buffer-coated fragments; The functional hybrid slurry is composed of sepiolite nanofibers, magnesium silicate sol, waterborne epoxy resin emulsion, waterborne epoxy resin curing agent and deionized water. S4: By weight, mix 30-50 parts of active magnesium oxide, 20-40 parts of magnesium chloride solution, 5-15 parts of mineral filler, and 1-3 parts of composite activator evenly, then add 15-35 parts of buffer-coated fragments obtained in step S3 and continue stirring until evenly dispersed to obtain composite slurry. S5: Pour the composite slurry obtained in step S4 into the mold, and apply ultrasonic vibration simultaneously during the pouring process to smooth the surface. S6: Demold the mold after curing. After demolding, place the board in a sealed curing room for carbonization curing. After carbonization curing, allow it to age naturally to obtain environmentally friendly magnesium oxide composite board.
[0012] As some possible implementations of this application, in step S1, the mechanical crushing is carried out to a particle size of 0.5~5mm, and the 1~3mm particle size fragments are sieved out. The volume ratio of oxygen to nitrogen is 1:1 to 1:3, the discharge power is 100 to 300W, the processing time is 3 to 15 minutes, and the discharge frequency is 13.56MHz or 40kHz.
[0013] As some possible implementations of this application, in step S2, the concentration of the active magnesium oxide-magnesium chloride precursor solution is 15-30 wt%, wherein the molar ratio of MgO to MgCl2 is 4-6:1; the stirring reaction is first stirred at 15-25°C for 30-60 min, then heated to 40-60°C and stirred for 1-2 h; the pre-curing temperature is 60-80°C, and the time is 4-8 h. In this scheme, the molar ratio of MgO to MgCl2 in the precursor solution is 4-6:1, which is within the formation range of 5.1.8 phase basic magnesium chloride, which is beneficial to the phase purity of the seed layer.
[0014] As some possible implementations of this application, in step S2, the nano-magnesium hydroxide nucleation promoter accounts for 1-3% of the total mass of the precursor solution; the particle size of the nano-magnesium hydroxide is 50-200 nm. In this scheme, the nano-magnesium hydroxide nucleation promoter accounts for 1-3% of the total mass of the precursor solution. If it is less than 1%, there will be insufficient nucleation sites and incomplete seed layer coverage; if it is more than 3%, it may lead to excessively high solution viscosity and affect impregnation uniformity. The particle size of the nano-magnesium hydroxide is 50-200 nm. If the particle size is too small, it is easy to agglomerate and difficult to disperse uniformly; if the particle size is too large, it is not conducive to the adsorption of particles on the surface of the crushed material.
[0015] As some possible implementations of this application, in step S3, the mass ratio of sepiolite nanofibers, magnesium silicate sol, aqueous epoxy resin emulsion, and deionized water in the functional hybrid slurry is (3~8):(10~20):(5~10):(60~80). When using the aqueous epoxy resin emulsion, a curing agent with the manufacturer's recommended proportion is added. The solid content of the magnesium silicate sol is 20~30%, and the solid content of the aqueous epoxy resin emulsion is 40~50%. In this scheme, at this mass ratio, magnesium silicate sol and sepiolite nanofibers, as inorganic components, constitute the majority, ensuring the carbonization inertness and gas slow-release function of the buffer layer. The moderate amount of aqueous epoxy resin emulsion imparts flexibility to the buffer layer while avoiding the adverse effects of excessive organic components on fire resistance.
[0016] As some possible implementations of this application, in step S3, the drying temperature is 50~70℃ and the drying time is 30~60min; the magnesium silicate sol is prepared by sodium silicate and magnesium sulfate by sol-gel method, and the molar ratio of MgO to SiO2 is 0.8~1.2:1.
[0017] As one possible implementation of this application, in step S3, the sepiolite nanofibers have a length of 0.5~2μm and a diameter of 20~50nm. In this embodiment, the sepiolite nanofibers have a length of 0.5~2μm and a diameter of 20~50nm. This size range is beneficial for the fibers to form an interwoven network in the buffer layer, increasing the tortuosity of the gas diffusion path, allowing the pyrolysis gas to escape smoothly outward along the tortuous channel, avoiding instantaneous concentrated release.
[0018] As one possible implementation of this application, in step S4, the composite activator is a combination of aluminum dihydrogen phosphate and magnesium silicate, and the mineral filler is selected from wollastonite powder, sepiolite powder, or brucite powder. In this scheme, the composite activator uses a combination of aluminum dihydrogen phosphate and magnesium silicate. Aluminum dihydrogen phosphate can provide phosphate ions, which form insoluble magnesium phosphate with magnesium ions during the slurry hydration stage, helping to improve the water resistance of the board; magnesium silicate can participate in the formation of magnesium silicate gel phase, improving the density of the matrix. The mechanisms of the two are complementary, synergistically improving the long-term durability of the board.
[0019] As some possible implementations of this application, in step S5, the frequency of the ultrasonic vibration is 20~50kHz, the power density is 0.5~2W / cm², and it is applied intermittently, with a 30~60s interval between vibrations and a 10~20s interval, and the total vibration time is 5~15min.
[0020] As some possible implementation methods of this application, the curing and demolding conditions in step S6 are: temperature 25~35℃, relative humidity 60%~80%RH, and time 24~48h; the carbonization curing conditions are: CO2 atmosphere, CO2 volume concentration 15%~30%, temperature 30~40℃, and time 3~7d; the natural aging conditions are: temperature 15~25℃, relative humidity 50%~65%RH, and time 7~14d. In this scheme, the CO2 volume concentration for carbonization curing is 15%~30%, the temperature is 30~40℃, and the time is 3~7d. Moderate carbonization can solidify free magnesium salts, improve water resistance and anti-reversion properties, while avoiding excessive carbonization that leads to loss of matrix strength. The carbonization products can decompose and absorb heat and release CO2 in a fire, which has a positive synergistic effect on the fire resistance of the board.
[0021] Compared with the prior art, the beneficial effects of the present invention are: The process for preparing environmentally friendly magnesium oxide composite boards based on solid waste from decommissioned wind turbine blades provided by this invention can improve upon the problems mentioned in the background technology, such as the inherent defects of blade pulverized materials at room temperature, the difficulty in balancing the performance and cost of traditional reinforcing fillers, and the damage to the boards caused by the transient pyrolysis of resin under high temperatures in a fire. Specifically, the process is as follows: In step S1, the decommissioned wind turbine blades are mechanically crushed and then subjected to low-temperature plasma treatment in a mixed atmosphere of oxygen and nitrogen. During the treatment, the fragments are continuously agitated, which erodes the weak interface layer of the resin layer on the surface of the fragments, removes surface-adhered impurities, and introduces oxygen- and nitrogen-containing polar groups onto the resin layer surface, making the surface rough. The introduction of polar groups improves the wettability of the resin layer surface to subsequent solutions, providing sites for the adhesion of magnesium ions in the subsequent precursor solution; the roughened surface provides more adhesion sites for subsequent seed nucleation.
[0022] In step S2, the activated fragments are immersed in an active magnesium oxide-magnesium chloride precursor solution containing a nano-magnesium hydroxide nucleation promoter. After stirring and reaction, the fragments are removed and pre-cured, resulting in a 5.1.8 phase basic magnesium chloride seed layer on the surface of the fragments. The nano-magnesium hydroxide nucleation promoter can be adsorbed onto the surface of the activated fragments, providing highly active sites for the heterogeneous nucleation of the 5.1.8 phase, promoting its uniform and dense formation. The chemical composition and crystal structure of the formed seed layer have a high crystallographic affinity with the main strength phase of the subsequent magnesium oxychloride cement matrix. During the slurry preparation stage, the matrix hydration products can continue to grow on the surface of the seed layer, improving the interfacial bonding between the fragments and the matrix. Under the high-temperature environment of a fire, the 5.1.8 phase seed layer gradually removes its water of crystallization and absorbs heat, delaying the interface temperature rise. Compared with the instantaneous pyrolysis failure of silane coupling agents at high temperatures, its decomposition process can prolong the duration of interfacial bonding. The volatile components generated during the decomposition process can be slowly released outward through the porous channels of the buffer layer, reducing the risk of local pressure buildup.
[0023] In step S3, the seed crystal fragments are impregnated in a functional hybrid slurry composed of sepiolite nanofibers, magnesium silicate sol, aqueous epoxy resin emulsion, and deionized water, and an interface buffer layer is coated on the surface of the fragments. In this buffer layer, the inorganic gel skeleton formed by the magnesium silicate sol and the sepiolite fiber network together constitute a dense protective layer. During the subsequent carbonization curing stage, the penetration rate of CO2 to the fragment interface can be controlled, preventing the seed crystal layer from prematurely and rapidly contacting high concentrations of CO2 and undergoing extensive carbonization decomposition. This allows the seed crystal layer to effectively function as a template during the slurry preparation stage without affecting the overall carbonization curing effect of the matrix. The sepiolite nanofibers have a layered chain structure and nanopores, which can overlap in the buffer layer to form a fiber network, constructing a tortuous and continuous gas diffusion channel. This allows the resin pyrolysis gas to escape smoothly outward along this channel, avoiding a concentrated release of large amounts of gas instantaneously, and reducing the risk of localized cracking of the board caused by gas pressure accumulation. Meanwhile, the sepiolite fiber network can absorb some of the impact energy during subsequent ultrasonic vibration, reducing mechanical erosion of the seed layer. The water-based epoxy resin emulsion imparts a certain degree of flexibility to the buffer layer, which can buffer the thermal mismatch stress between the debris and the matrix when the temperature changes, reducing the initiation of microcracks. The amount of water-based epoxy resin added to the buffer layer is controlled, and the proportion of organic components is low. Under the high temperature of a fire, the epoxy resin is carbonized in a controlled manner, without damaging the gas conduction function of the sepiolite fiber network. The total amount of organic components is insufficient to affect the overall Class A non-combustible properties of the board.
[0024] In step S4, active magnesium oxide, magnesium chloride solution, mineral filler, and composite activator are mixed in proportion, and then buffer-coated crushed material is added and stirred until uniformly dispersed. The amount of buffer-coated crushed material is 15-35 parts. While achieving high filling of waste materials, the seed layer and buffer layer on the surface of the crushed material enable good compatibility between the crushed material and the magnesium cement paste, which helps the crushed material to be uniformly dispersed in the matrix.
[0025] In step S5, ultrasonic vibration is applied simultaneously during the casting process. Intermittent low-to-medium power ultrasound is used, and the resulting cavitation effect can break up any fiber agglomerates that may exist in the slurry, promoting the uniform dispersion of the fragments in the matrix and the densification of the slurry, reducing stress concentration areas formed inside the product due to fiber agglomeration; at the same time, the toughness of the buffer layer buffers the ultrasonic cavitation impact, reducing the risk of the coating layer and seed layer falling off from the surface of the fragments.
[0026] In step S6, after demolding from the mold, carbonization curing is performed, followed by natural aging. CO2 carbonization curing causes the free magnesium oxide and magnesium hydroxide in the board to react with CO2 to form a carbonate phase, which can improve the density of the matrix and the water resistance of the board. Moderate carbonization can solidify free magnesium salts and significantly reduce the tendency for efflorescence. The carbonization products can decompose and absorb heat and release CO2 under high temperatures in a fire, which has a positive effect on the fire resistance of the board; at the same time, excessive carbonization should be avoided to prevent damage to the matrix strength. Natural aging allows the internal moisture of the board to evaporate slowly, and the carbonate phase is further stabilized, which helps to further reduce the risk of efflorescence.
[0027] In summary, this invention improves the interfacial compatibility and dispersion uniformity of the scrap material and the matrix at room temperature through low-temperature plasma treatment, pre-planting of crystal seeds, and coating with an interface buffer layer. It also delays the structural failure of the plate under fire conditions, providing a process route for the resource utilization of solid waste from decommissioned wind turbine blades in magnesium oxide composite plates for fire-resistant load-bearing components. Detailed Implementation
[0028] Example 1 S1. Collect decommissioned wind turbine blades. The blade matrix is epoxy resin / glass fiber composite material. After cutting and coarse crushing, mechanically crush them to a particle size of 0.5~5mm using a hammer crusher. Then, sieve and classify the material to obtain 1~3mm particle size fragments. Place 500g of the fragments in a rotating drum of a low-temperature plasma treatment chamber. After evacuating to 10Pa, introduce a mixture of oxygen and nitrogen in a volume ratio of 1:2, maintaining the chamber pressure at 50Pa. Set the discharge frequency to 13.56MHz and the discharge power to 200W, and treat for 10 minutes under the condition that the drum continuously rotates, causing the fragments to tumble. After treatment, remove the fragments to obtain activated fragments.
[0029] S2. Immerse 400g of the activated fragments obtained in step S1 into 800mL of an active magnesium oxide-magnesium chloride precursor solution. First, stir in a 20℃ water bath for 45min, then raise the temperature to 50℃ and continue stirring for 1.5h. After the reaction is complete, remove the fragments and pre-cur them in a 70℃ forced-air drying oven for 6h to obtain seeded fragments.
[0030] The preparation method of the active magnesium oxide-magnesium chloride precursor solution is as follows: Add active magnesium oxide powder (industrial grade, MgO content ≥85%, activity ≥60%) to deionized water and stir for 30 min to pre-hydrate, controlling the mass ratio of MgO to water to be 1:5; dissolve magnesium chloride (industrial grade) in deionized water to prepare a magnesium chloride solution with a concentration of 25wt%; slowly add the pre-hydrated magnesium oxide slurry to the magnesium chloride solution, controlling the final molar ratio of MgO to MgCl2 to be 5:1, and stir evenly; add 2% of nano magnesium hydroxide nucleation promoter according to the total mass of the precursor solution, stir and disperse evenly, and use within 2 hours after preparation.
[0031] The preparation method of the nano-magnesium hydroxide nucleation promoter is as follows: magnesium chloride (analytical grade) is dissolved in deionized water to prepare a magnesium chloride solution with a concentration of 0.2 mol / L; sodium hydroxide (analytical grade) is dissolved in deionized water to prepare a sodium hydroxide solution with a concentration of 0.4 mol / L; under stirring conditions at room temperature, the magnesium chloride solution is slowly added dropwise to an equal volume of sodium hydroxide solution, and stirring is continued for 15 min after the addition is completed; the resulting suspension is transferred to a high-pressure reactor and hydrothermally treated at 120℃ for 4 h, and after natural cooling, it is centrifuged and separated. The precipitate is washed with deionized water until the pH of the washing solution is neutral, and then washed once with anhydrous ethanol. It is then vacuum dried at 80℃ for 6 h, and after grinding, nano-magnesium hydroxide with a particle size of 80~150 nm is obtained.
[0032] S3. Immerse 350g of the seeded fragments obtained in step S2 into 600mL of functional hybrid slurry and stir at 80r / min for 10min at room temperature. Remove the fragments, drain off excess slurry, spread them evenly on a stainless steel tray, and dry them in a 60℃ forced-air drying oven for 45min to obtain buffer-coated fragments.
[0033] The preparation method of the functional hybrid slurry is as follows: Weigh 5 parts of sepiolite nanofiber, 15 parts of magnesium silicate sol (solid content 25%), 8 parts of waterborne epoxy resin emulsion (solid content 45%, commercially available two-component room temperature curing type), and 72 parts of deionized water according to the following mass ratio: First, add the sepiolite nanofiber to the deionized water and ultrasonically disperse for 10 minutes. Then, add the magnesium silicate sol and stir evenly. Finally, add the waterborne epoxy resin emulsion and the matching curing agent (according to the emulsion manufacturer's recommended dosage) and stir for 10 minutes until uniform. The functional hybrid slurry is then obtained and should be prepared and used immediately.
[0034] The preparation method of magnesium silicate sol is as follows: sodium silicate (industrial grade) is dissolved in deionized water to prepare a sodium silicate solution with a concentration of 0.5 mol / L; magnesium sulfate (industrial grade) is dissolved in deionized water to prepare a magnesium sulfate solution with a concentration of 0.5 mol / L; under stirring conditions at room temperature, the sodium silicate solution is slowly added dropwise to the magnesium sulfate solution, controlling the molar ratio of MgO to SiO2 to be 1:1. After the addition is complete, stirring is continued for 30 min, and the solution is allowed to stand for 2 h to obtain magnesium silicate sol; the sol is repeatedly washed with deionized water until the conductivity of the washing solution is lower than 100 μS / cm to remove the byproduct sodium sulfate; finally, water is added to adjust the solid content to 25%, and the solution is sealed and stored for use within 24 h.
[0035] The preparation method of sepiolite nanofibers is as follows: natural sepiolite ore is crushed and purified by water separation, and then mixed with water at a mass ratio of 1:20 to form a suspension. 0.5% of sodium polyacrylate dispersant is added to the total mass of the suspension. The suspension is ball-milled at a speed of 400 r / min for 4 h, and then ultrasonically exfoliated at a power of 200 W for 30 min. The exfoliated suspension is centrifuged and classified, and the precipitate is collected and redispersed in deionized water. The washing-centrifugation operation is repeated 3 times. The precipitate is freeze-dried to obtain sepiolite nanofibers with a length of 0.5~1.5 μm and a diameter of 25~45 nm.
[0036] S4. Weigh out 40 parts by weight of activated magnesium oxide (industrial grade, MgO content ≥85%, activity ≥60%), 30 parts by weight of magnesium chloride solution (concentration 25°Bé, prepared from industrial grade magnesium chloride), 10 parts by weight of wollastonite powder (fineness 400 mesh), and 2 parts by weight of composite activator. First, mix the magnesium chloride solution and composite activator evenly, then add the activated magnesium oxide and wollastonite powder, and stir at 200 r / min for 5 min until a uniform slurry is formed. Then add 25 parts by weight of the buffer-coated fragments obtained in step S3, and continue stirring at 150 r / min for 8 min until the fragments are evenly dispersed in the slurry to obtain the composite slurry.
[0037] The composite activator is prepared by mixing aluminum dihydrogen phosphate (industrial grade) and amorphous magnesium silicate powder obtained by drying and grinding magnesium silicate sol at a mass ratio of 1:2.
[0038] S5: Pour the composite slurry obtained in step S4 into a steel mold with dimensions of 300mm × 300mm, with a pouring thickness of 10mm. During the pouring process, ultrasonic vibration is applied simultaneously at a frequency of 35kHz and a power density of 1.0W / cm², using an intermittent application method (45s vibration followed by a 15s interval), with a total vibration time of 10min. After vibration, the surface is smoothed.
[0039] S6: Place the mold in a curing chamber at 30℃ and 70%RH for 36 hours, then demold. After demolding, transfer the board to a sealed carbonization curing chamber, introduce a CO2 atmosphere with a volume concentration of 20%, and carbonize at 35℃ for 5 days. After carbonization curing, place the board in an environment at 20℃ and 55%RH for 10 days to age naturally, thus obtaining the environmentally friendly magnesium oxide composite board.
[0040] Example 2 This embodiment adjusts some parameters based on embodiment 1. All other parameters are the same as in embodiment 1, unless otherwise mentioned. The specific adjustments are as follows: S1: Oxygen to nitrogen volume ratio 1:1, discharge power 100W, discharge frequency 40kHz, treatment time 3min.
[0041] S2: The precursor solution concentration is 15wt%, the molar ratio of MgO to MgC2 is 4:1. First, stir at 15℃ for 30min, then raise the temperature to 40℃ and continue stirring for 2h. The pre-curing temperature is 60℃ and the time is 8h.
[0042] S3: The mass ratio of sepiolite nanofibers, magnesium silicate sol, waterborne epoxy resin emulsion, and deionized water in the hybrid slurry is 3:20:5:72, of which the magnesium silicate sol has a solid content of 20% and the waterborne epoxy resin emulsion has a solid content of 40%; the drying temperature is 50℃ and the time is 60min.
[0043] S4: The slurry composition is 30 parts active magnesium oxide, 40 parts magnesium chloride solution, 5 parts wollastonite powder, 1 part composite activator, and 15 parts buffer coating fragments.
[0044] S5: Ultrasonic frequency 20kHz, power density 0.5W / cm², 30s vibration interval with 10s pause, total vibration time 5min.
[0045] S6: Curing and demolding conditions are 25℃ temperature, 80%RH relative humidity, and 24h time; carbonization curing conditions are 15% CO2 volume concentration, 30℃ temperature, and 7d time; natural aging conditions are 15℃ temperature and 65%RH relative humidity and 7d time.
[0046] Example 3 This embodiment adjusts some parameters based on embodiment 1. All other parameters are the same as in embodiment 1, unless otherwise mentioned. The specific adjustments are as follows: S1: Oxygen to nitrogen volume ratio 1:3, discharge power 300W, treatment time 15min.
[0047] S2: The precursor solution concentration is 30wt%, the molar ratio of MgO to MgCl2 is 6:1, and the mixture is stirred at 25℃ for 60min, then heated to 60℃ and stirred for 1h. The pre-curing temperature is 80℃ and the time is 4h.
[0048] S3: The mass ratio of sepiolite nanofibers, magnesium silicate sol, waterborne epoxy resin emulsion, and deionized water in the hybrid slurry is 8:10:10:72, of which the solid content of magnesium silicate sol is 30% and the solid content of waterborne epoxy resin emulsion is 50%; the drying temperature is 70℃ and the time is 30min.
[0049] S4: The slurry composition is 50 parts active magnesium oxide, 20 parts magnesium chloride solution, 15 parts wollastonite powder, 3 parts composite activator, and 35 parts buffer coating fragments.
[0050] S5: Ultrasonic frequency 50kHz, power density 2.0W / cm², 60s vibration interval with 20s pause, total vibration time 15min.
[0051] S6: Curing and demolding conditions are 35℃ temperature, 60%RH relative humidity, and 48h time; carbonization curing conditions are 30% CO2 volume concentration, 40℃ temperature, and 3d time; natural aging conditions are 25℃ temperature, 50%RH relative humidity, and 14d time.
[0052] Comparative Example 1 This comparative example omits the S1 low-temperature plasma surface activation step, based on Example 1. The decommissioned wind turbine blades are mechanically crushed to a particle size of 0.5-5 mm, and after sieving to obtain 1-3 mm particle size fragments, no low-temperature plasma treatment is performed; these fragments are directly used for S2 seed pre-planting. The remaining steps and parameters are the same as in Example 1.
[0053] Comparative Example 2 This comparative example omits the S2 active magnesium crystal pre-planting step, which is based on Example 1. Instead, the activated fragments obtained in S1 are directly coated with the S3 interface buffer layer without undergoing crystal pre-planting. The remaining steps and parameters are the same as in Example 1.
[0054] Comparative Example 3 This comparative example omits the S3 interface buffer layer coating step, based on Example 1. That is, the seeded fragments obtained in S2 are used directly for S4 slurry preparation without buffer layer coating. The remaining steps and parameters are the same as in Example 1.
[0055] Comparative Example 4 This comparative example omits the S6 carbonization curing step, which is based on Example 1. That is, only curing demolding and natural aging are performed in S6, without CO2 carbonization curing. After curing demolding, the boards are naturally cured for 15 days at 20°C and 55% RH. The remaining steps and parameters are the same as in Example 1.
[0056] Comparative Example 5 This comparative example is based on Example 1, except that the pre-implantation of the S2 crystal seeds was replaced with silane coupling agent treatment. Specifically, 400g of the activated fragments obtained in S1 were immersed in 800mL of a 3wt% γ-aminopropyltriethoxysilane (KH-550) ethanol solution for 1 hour at room temperature, and then dried at 70°C for 6 hours to obtain coupling agent-treated fragments. Subsequent steps S3, S4, S5, and S6 and their parameters were the same as in Example 1, except that the seeded fragments were replaced with coupling agent-treated fragments.
[0057] Comparative Example 6 This comparative example differs from Example 1 by replacing the S3 interface buffer layer with a pure water-based epoxy resin coating. Specifically, 350g of the seeded fragments obtained in S2 were immersed in 600mL of water-based epoxy resin emulsion (solid content 45%, diluted with deionized water to the same solid content as the hybrid slurry in Example 1), stirred at room temperature for 10min, and then dried at 60℃ for 45min. Subsequent steps and parameters in S4, S5, and S6 were the same as in Example 1.
[0058] Experimental Example The environmentally friendly magnesium oxide composite boards obtained in Examples 1-3 (denoted as S1-S3) and the composite boards obtained in Comparative Examples 1-6 (denoted as D1-D6) were used as test samples. All samples were cut from 300mm×300mm×10mm boards prepared in the same batch, with the required dimensions cut from the central area of the board, avoiding the mold edge within 50mm. Three parallel repeated experiments were simultaneously set up for each group of samples. The average value of the three parallel tests was taken as the final test result, with a relative standard deviation (RSD) ≤ 5%. The test results are shown in Table 1. The test items and methods are as follows: 1. Flexural strength test: The specimen dimensions are 250mm × 50mm × 10mm. The specimen is placed on a universal testing machine with a span of 200mm and a loading rate of 5mm / min. The maximum load at which the specimen breaks is recorded, and the flexural strength is calculated using the three-point bending formula.
[0059] 2. Non-flammability test: The non-combustibility test was conducted according to the standard method for building materials. The specimen was a cylinder with a diameter of 45 mm and a height of 50 mm, drilled from the sheet material. The furnace temperature rise, mass loss rate, and flame duration were recorded to determine the non-combustibility rating.
[0060] 3. Fire resistance limit test: The fire resistance test shall be conducted according to the method for building components. The specimen size is 300mm×300mm×10mm, and one side is exposed to fire. Record the time when the temperature of the unexposed side reaches 180℃ or when flame penetration occurs.
[0061] 4. Post-fire structural integrity observation: After the fire resistance limit test is completed, allow the specimen to cool naturally to room temperature, observe and record the overall condition of the specimen, and evaluate it according to the following levels: Grade I: The surface has a small number of fine cracks, all of which are no more than 5 mm in length, with no through cracks and no delamination; Level II: Non-penetrating cracks with a length exceeding 5mm appear on the surface, without penetrating cracks or delamination; Level III: 1 to 3 through cracks appear, or local peeling occurs, but no delamination or overall collapse occurs; Level IV: Three or more through cracks appear, or there is delamination, large-area peeling, or overall collapse.
[0062] 5. Interface bonding strength test: The interfacial bond strength between the scrap and the matrix was tested using the pull-out method. A steel pull-out head with a diameter of 50 mm was bonded to the surface of the specimen (100 mm × 50 mm × 10 mm) with epoxy resin adhesive. After curing, the specimen was pulled out using a pull-out testing machine at a rate of 2 mm / min. The maximum load at failure was recorded, and the interfacial bond strength was calculated.
[0063] 6. Observation of microcracks during heat-humidity cycling: The specimen dimensions were 100mm × 100mm × 10mm. The specimen was placed in a 60℃ forced-air drying oven for 8 hours, then immediately immersed in a 20℃ water bath for 8 hours; this constituted one cycle. After 30 cycles, the specimen was removed and observed under a stereomicroscope at 20x magnification on the surface and cross-section. The number of microcracks longer than 0.5mm per unit area (10mm × 10mm field of view) was counted. Five fields of view were randomly selected from each specimen for statistical analysis, and the average value was taken. The number of microcracks is the average value of the five fields of view counts.
[0064] 7. Water resistance test (softening coefficient): The specimen dimensions are 250mm × 50mm × 10mm. After immersing the specimen in water at 20℃ for 24 hours, remove it, wipe off the surface moisture, and immediately test its flexural strength according to the above-described flexural strength test method. The ratio of the flexural strength after immersion to that before immersion is used as the softening coefficient.
[0065] 8. Long-term wet maintenance volume stability test: The specimen dimensions are 100mm×100mm×10mm. After curing in a curing room at a temperature of 25±2℃ and a relative humidity of ≥95%RH for 28 days, the specimen was removed. First, the specimen surface was observed for micro-cracks. Then, the specimen surface was observed under natural light for white crystalline precipitates or damp water stains. If there were no white crystalline precipitates and no damp water stains, it was determined that there was no efflorescence phenomenon. Afterward, the change in length of each side of the specimen was measured with vernier calipers, and the volume expansion rate was calculated.
[0066] Table 1 Performance test results of each sample As can be seen from Table 1: The boards obtained in Examples S1-S3 all exhibited excellent mechanical properties, fire resistance, and long-term durability at room temperature, improving upon the inherent defects of blade crushed materials at room temperature, the difficulty in balancing the performance and cost of traditional reinforcing fillers, and the damage caused by transient pyrolysis of resin under high temperatures during fires, as mentioned in the background art. Specifically, the flexural strength all reached over 16.5 MPa, and the interfacial bonding strength all reached over 2.7 MPa, indicating that the triple interface design of plasma activation, pre-implantation of crystals, and buffer layer coating effectively improved the interfacial compatibility between the crushed material and the magnesium cement matrix. The crushed material was evenly dispersed in the matrix, with no obvious stress concentration areas. The non-combustibility was Class A, the fire resistance limit exceeded 120 min, and the structural integrity after fire reached Class I, indicating that the boards have good structural stability under fire conditions. The progressive endothermic decomposition of the crystal layer, the gas slow-release effect of the sepiolite fiber network, and the synergistic protection of carbonization products formed an effective fire protection mechanism, delaying the structural failure of the boards during fires. After heat-humidity cycling, the average number of microcracks per unit field of view was only 0.5~0.7, indicating that the flexibility of the epoxy resin in the buffer layer and the elastic buffering effect of the sepiolite fiber effectively adapted to the thermal mismatch stress between the crushed material and the matrix, reducing the accumulation of micro-damage under daily use conditions. The softening coefficients all reached above 0.87, the volume expansion rate under long-term wet curing did not exceed 0.19%, and there was no efflorescence phenomenon, indicating that the synergistic effect of CO2 carbonization curing and composite activator improved the density and water resistance of the board.
[0067] After omitting the S1 plasma activation step in Comparative Example D1, the interfacial bonding strength and flexural strength both decreased significantly, the fire resistance limit decreased, and edge peeling and cracks appeared after the fire. The number of microcracks in the heat-moisture cycle increased, indicating that the lack of polar groups and rough structure on the surface of the fragments are not conducive to the uniform nucleation of the subsequent seed layer.
[0068] Comparative Example D2, after omitting the S2 seeding step, showed the most significant deterioration in various properties, the lowest interfacial bonding strength, a greatly shortened fire resistance limit, and the appearance of delamination and multiple through cracks after the fire. It also showed the highest number of microcracks due to heat-humidity cycling. This indicates that the 5·1·8 phase seed layer plays an important role in interfacial bonding and fire protection.
[0069] Comparative Example D3, after omitting the S3 buffer layer coating step, showed a significantly shortened fire resistance limit and the appearance of through cracks and local delamination after the fire, reflecting the importance of the buffer layer in protecting the seed layer during carbonization curing and providing a gas release channel during the fire.
[0070] Comparative Example D4, after omitting the S6 carbonization curing step, showed a decrease in softening coefficient, an increase in volume expansion rate, and significant efflorescence, indicating that carbonization curing is indispensable for improving the water resistance and volume stability of the board.
[0071] Comparative Example D5, after replacing the pre-planted seed crystals with silane coupling agent, had its fire resistance limit reduced to the minimum, and severe delamination and peeling occurred after the fire, proving that the coupling agent cannot replace the progressive endothermic decomposition protection function of the seed crystal layer under high fire temperatures.
[0072] In Comparative Example D6, after the buffer layer was replaced with pure epoxy resin coating, the fire resistance limit decreased, and surface peeling and through cracks appeared after the fire. The number of microcracks in the heat-moisture cycle increased, indicating that the single epoxy resin layer lacks the ability to protect the seed layer from carbonization and to slow down gas release.
Claims
1. A process for preparing environmentally friendly magnesium oxide composite panels based on solid waste from decommissioned wind turbine blades, characterized in that, Includes the following steps: S1: Mechanically crush the retired wind turbine blades and place them in a low-temperature plasma treatment chamber for treatment in a mixed atmosphere of oxygen and nitrogen. During the treatment process, the crushed material is continuously turned over to obtain activated crushed material. S2: The activated fragments obtained in step S1 are immersed in an active magnesium oxide-magnesium chloride precursor solution, stirred and reacted, and then taken out for pre-curing to obtain seeded fragments; the precursor solution contains nano-magnesium hydroxide nucleation promoter; S3: Immerse the seeded fragments obtained in step S2 in the functional hybrid slurry, stir, and then take them out and dry them to obtain buffer-coated fragments; The functional hybrid slurry is composed of sepiolite nanofibers, magnesium silicate sol, aqueous epoxy resin emulsion, and deionized water. S4: By weight, mix 30-50 parts of active magnesium oxide, 20-40 parts of magnesium chloride solution, 5-15 parts of mineral filler, and 1-3 parts of composite activator evenly, then add 15-35 parts of buffer-coated crushed material obtained in step S3 and continue stirring until evenly dispersed to obtain composite slurry. S5: Pour the composite slurry obtained in step S4 into the mold, and apply ultrasonic vibration simultaneously during the pouring process to smooth the surface; S6: Demold the mold after curing. After demolding, place the board in a sealed curing room for carbonization curing. After carbonization curing, allow it to age naturally to obtain environmentally friendly magnesium oxide composite board.
2. The process according to claim 1, characterized in that, In step S1, the mechanical crushing is carried out to a particle size of 0.5~5mm, and the 1~3mm particle size fragments are sieved out; The volume ratio of oxygen to nitrogen is 1:1 to 1:3, the discharge power is 100 to 300W, the processing time is 3 to 15 minutes, and the discharge frequency is 13.56MHz or 40kHz.
3. The process according to claim 1, characterized in that, In step S2, the concentration of the active magnesium oxide-magnesium chloride precursor solution is 15-30 wt%, wherein the molar ratio of MgO to MgCl2 is 4-6:1; the stirring reaction is carried out by stirring at 15-25℃ for 30-60 min, and then heating to 40-60℃ and continuing stirring reaction for 1-2 h; the pre-curing temperature is 60-80℃ and the time is 4-8 h.
4. The process according to claim 1, characterized in that, In step S2, the nano-magnesium hydroxide nucleation promoter accounts for 1-3% of the total mass of the precursor solution; the particle size of the nano-magnesium hydroxide is 50-200 nm.
5. The process according to claim 1, characterized in that, In step S3, the mass ratio of sepiolite nanofibers, magnesium silicate sol, aqueous epoxy resin emulsion and deionized water in the functional hybrid slurry is (3~8):(10~20):(5~10):(60~80), wherein the solid content of magnesium silicate sol is 20~30% and the solid content of aqueous epoxy resin emulsion is 40~50%.
6. The process according to claim 1, characterized in that, In step S3, the drying temperature is 50~70℃ and the drying time is 30~60min; the magnesium silicate sol is prepared by sodium silicate and magnesium sulfate by sol-gel method, and the molar ratio of MgO to SiO2 is 0.8~1.2:
1.
7. The process according to claim 1, characterized in that, In step S3, the sepiolite nanofibers have a length of 0.5~2μm and a diameter of 20~50nm.
8. The process according to claim 1, characterized in that, In step S4, the composite activator is a combination of aluminum dihydrogen phosphate and magnesium silicate, and the mineral filler is selected from wollastonite powder, sepiolite powder or brucite powder.
9. The process according to claim 1, characterized in that, In step S5, the frequency of the ultrasonic vibration is 20~50kHz, the power density is 0.5~2W / cm², and it is applied intermittently, with a 30~60s interval between vibrations and a 10~20s interval, for a total vibration time of 5~15min.
10. The process according to claim 1, characterized in that, The curing and demolding conditions in step S6 are: temperature 25~35℃, relative humidity 60~80%, time 24~48h; the carbonization curing conditions are: CO2 atmosphere, CO2 concentration 15~30 vol%, temperature 30~40℃, time 3~7d; the natural aging conditions are: temperature 15~25℃, relative humidity 50~65%, time 7~14d.